1990
DOI: 10.1007/bf00294608
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural investigation of the CA1 region of the hippocampus after transient cerebral ischemia in gerbils

Abstract: Ultrastructural damage leading to delayed neuronal death was investigated in the mid-CA1 region of the hippocampus from the stratum (str.) moleculare to oriens after transient bilateral forebrain ischemia in Mongolian gerbils. After ischemia for 5 min without recirculation, mild swelling of the peripheral part of the apical and basal dendrites was already apparent in the str. moleculare and str. oriens. Mitochondria in the dendrites were also swollen in the same area. During recirculation for 12 h to 3 days, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…14 Also an EM study on the CA-1 showed degeneration and shrinkage of dendrite around 3 to 4 days after temporary ischemia. [15][16][17] In the present study, we found that the neurites degenerated around 4 days and that their thickness increased, in association with the recovery to normal of the number and percent volume of spines, at 12 weeks after the insult.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…14 Also an EM study on the CA-1 showed degeneration and shrinkage of dendrite around 3 to 4 days after temporary ischemia. [15][16][17] In the present study, we found that the neurites degenerated around 4 days and that their thickness increased, in association with the recovery to normal of the number and percent volume of spines, at 12 weeks after the insult.…”
Section: Discussionsupporting
confidence: 62%
“…10 Changes in spines and dendrites were studied by time-lapse microscopy after temporary anoxia/hypoglycemia in cell culture, 11,12 by light microscopy (LMS) of Golgi stain-impregnated sections of the 3rd to 5th cortical layers of the cerebral cortex after temporary ischemia, 13 and by EM after temporary hypoxia/glycemia in hippocampal slice. 10 Changes in CA-1 dendrites after temporary ischemia were investigated by light microscopy of horseradish peroxidase-injected specimens, 14 by EM after temporary ischemia in CA-1, 15,16 and by EM of Golgi stain-impregnated cerebral cortex after temporary ischemia for 20 minutes. 17 Almost all of the above studies were performed in connection with delayed ischemia-induced injury to CA-1 neurons, and observations were made during a short period after ischemia.…”
mentioning
confidence: 99%
“…1. 2000 NEURONAL APOPTOSIS AND mGluR AFTER ISCHEMIA 165 sidering the postsynaptic, somatodendritic localization of these proteins (Martin et al, 1992; Blue et al, 1997) and the rapid damage to dendritic membranes and the cytoskeletal proteolysis that occur in these neurons after ischemia (Kitagawa et al, 1989;Yamamoto et al, 1990). These abnormalities further support our conclusion that hippocampal pyramidal neurons and Purkinje cells undergo necrosis after ischemia.…”
supporting
confidence: 77%
“…These structural changes are consistent with the finding that total protein synthesis is severely reduced by 6 hours after transient global forebrain ischemia and is reduced persistently in CA1 neurons, with the vast majority of pyramidal neurons never regaining their normal biosynthetic activity (Thilmann et al, 1986; Johansen and Diemer, 1990; Furuta et al, 1993). Cytoskeletal disintegration also occurs early after ischemia, particularly in dendrites, before the degeneration of neuronal cell bodies (Kitagawa et al, 1989;Yamamoto et al, 1990). This rapid disassembly and proteolysis of the cytoskeleton after ischemia (Kitagawa et al, 1989) contrast with the organized structure of the cytoskeleton and the cytoskeletal accumulation in neurons undergoing apoptosis (see Fig.…”
mentioning
confidence: 99%
“…Early changes such as disaggregation of polyribosomes and dilated organelles 1,4,5 precede the eventual death of CA1 cells, which exhibits the typical features of necrosis (ie, mitochondrial flocculent densities, clumped chromatin, membrane breaks). [4][5][6] However, studies assessing DNA fragmentation after global ischemia have suggested biochemical See Editorial Comment, page 667 evidence for apoptosis. [7][8][9][10][11] In addition, findings of CA1 neuroprotection with protein synthesis inhibitors, such as cycloheximide or anisomycin, [12][13][14] suggest pharmacological evidence for apoptosis since this may depend on new protein synthesis.…”
mentioning
confidence: 99%